Understanding Islamic Dialectics in The Relationship with Local Culture in Buton Architecture Design - Muhammad Alifuddin; Alhamuddin Alhamuddin; Andri Rosadi; Eko Ariwidodo (Karsa: Journal of Social and Islamic Culture, 2021)
This study aimed to describe the shape and meaning of the architectural design of the Buton house both from an emic and ethical perspective. The focus of the problem was: (1). What was the shape and pattern of the house layout of the Butonese people? (2). What was the meaning of the traditional house architecture of the Butonese people? The data were obtained through a series of interviews, non-participant observation, and document review. All data were analyzed through some stages: formulation of questions, making descriptive narratives, data reduction, application, and interpretation, then concluding. Based on an analysis of the research problem, the following conclusions were obtained: (1). The shape of the Buton house had an aesthetic meaning related to belief or the dimension of religiosity, in this case, Islam; (2). The patron or pattern of the Butonese house building had become part of their system of thinking, so that eventually it became something standards, such as the standard of spatial structure, shape, structure, and ornamentation. In subsequent developments, there appeared to be an internal effort by the Butonese to provide a new perspective on the meaning of the Buton house, leading to interpretations oriented to Islamic values. The form of houses on stilts as depicted in malige and kamali by the local community was interpreted as a replica of a Muslim performing the prayer ritual. The model of a tiled roof was analogous to the composition or position when he was praying, where the place of the right hand was above the left hand. Whereas in the perspective of political power, the tiled roof was a symbol of political and religious unity. Pineapple ornaments played a role as a symbol of monotheism. This symbol also is a manifestation of the religious ethics Butonese, who always direct their life to the values ​​of monotheism.